2003
DOI: 10.1080/15627020.2003.11407280
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the estuarine-dependent sparidAcanthopagrus berdain northern KwaZulu-Natal, South Africa

Abstract: Ages were estimated for the tropical sparid, Acanthopagrus berda, caught in northern KwaZulu-Natal estuaries. Whole otoliths were used in the age determination. Age estimates were validated by marginal increment analysis and oxytetracycline labelling, which indicated that opaque deposition occurs primarily from September to November each year. The reproducibility of age estimates was described by a coefficient of variation of 10%. The von Bertalanffy growth curve was found to best describe the growth of A. ber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…Further, histological observation of transitional gonads in the current study showed signs of degeneration in the testicular lobe, the proliferation of connective tissue and empty sperm ducts which further confirms the protandrous sex change in A. berda collected from tropical Indian waters. The protandrous hermaphroditism in A. berda has been reported earlier in the African (Garratt, ; James et al, ) and Australian waters (Tobin et al, ). Sadovy and Shapiro () stated that the gonads of fish undergoing sex change may be expected to show degeneration of the germinal tissue of the primary sex accompanied by the proliferation of the tissue of the opposite sex.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Further, histological observation of transitional gonads in the current study showed signs of degeneration in the testicular lobe, the proliferation of connective tissue and empty sperm ducts which further confirms the protandrous sex change in A. berda collected from tropical Indian waters. The protandrous hermaphroditism in A. berda has been reported earlier in the African (Garratt, ; James et al, ) and Australian waters (Tobin et al, ). Sadovy and Shapiro () stated that the gonads of fish undergoing sex change may be expected to show degeneration of the germinal tissue of the primary sex accompanied by the proliferation of the tissue of the opposite sex.…”
Section: Discussionsupporting
confidence: 59%
“…The flesh of A. berda is excellent and therefore they are locally exploited by artisanal fisheries both in cast net and hook and line along the Indian coasts (FAO, ) and are sold fresh in markets (Shilta et al, ). This species is considered as an important commercial sparid fish (Kasahara, ) because of its recreational value, excellent meat quality, high economic value, ability to tolerate wide variations in salinity and temperature, easy adaptation to captivity and fast growth rate (Anonymous, ; Battaglene & Fielder, ; James, Mann, Beckely, & Govender, ; Rahim, Abbas, Ferrando, Gallus, & Ghaffar, ; Sadek, Osman, & Mansour, ; Samuel & Mathews, ; Thorogood & Blackshaw, ). This species in tropical Indian waters has the potential to attract commercial interests in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Estuarine resident fish species are predominantly small‐sized taxa when adults (Whitfield, 1990), and often dominate estuaries in terms of fish numbers but not in terms of biomass (Beckley, 1984; Cowley & Whitfield, 2002). Many reach sexual maturity in their first year (Ratte, 1989) and are short‐lived when compared to marine species using estuaries as primary nursery areas (James et al, 2003). Clupeids and atherinids, in particular, are important prey fish for the piscivorous marine species and, in some cases, most of the population does not attain 2 years of age (Talbot, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…As most of the sparid fishes, A. bifasciatus is characterized by long lifespan and slow rate of growth [7,19]. The long lifespan was recorded for Oceanography & Fisheries Open access Journal a number of Achanthopagrus species (i.e., 24 for A. latus; 17 for A. berda; up to 21 for A. butcheri; 29 and 31 for Acanthopagrus hybrid complexes; 28 for A. schlegelii) [19,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%